Warisan Budaya Dunia “Batik” sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing dalam Mendukung Internasionalisasi Bahasa Indonesia - Aisyah Kharisma Yogi; Syahla Ayu Yasinta; Risa Nurul Akbar; Syifa Rahmi Fauzani; Kundharu Saddono (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Batik is one of Indonesia's cultural heritages which was recognized by UNESCO on October 2 2009. The word "batik" comes from two Javanese terms, namely "amba" and "nitik" which means write and dot. This cultural heritage from Solo can be a means to deepen the experience of learning language and culture. This research found that adding batik to the BIPA curriculum can increase participant engagement and encourage their interest in Indonesian. The results show that Batik is not only a cultural heritage but also a bridge between language and culture. The integration of cultural elements in Indonesian language learning can provide a real picture, making it easier for BIPA students to understand. These results can be used as a guide for BIPA teachers, educational institutions, and related parties to create learning strategies that are in line with the internationalization of Indonesian.